"Soft, airy fairy stuff"? Re-evaluating 'social impacts' in gendered processes of natural resource extraction. (May 2018) - Ey, Melina
Abstract: Within the global extractive industry, emotions continue to the subject of regulation and erasure. In recent years, the dismissal of emotion within much of the extractive sector has been underpinned by particular hegemonic forms of masculinity which position emotions as 'irrational' and 'irrelevant'. The ramifications for the way in which this form of masculinity dismisses and erases emotion have been critiqued primarily within the context of those working within the sector (Mayes and Pini 2010, 2014; Pini et al 2010). However, this intervention has yet to take place to the same extent for those outside the sector, who are navigating its consequences for their communities and places. This paper argues that dismissing emotion has particular implications for the ways in which 'social impact assessments' are conducted, and for what is counted or classified as a 'social impact' by the sector. Drawing on women's experiences of opposition to the development of extractive projects throughout the New South Wales (NSW) Hunter Valley, this paper uses emotional geographies to emphasise the ways in which the masculinist regulation and erasure of emotion within the extractive sector also facilitates the dismissal of the distinctly emotional consequences of resource extraction for people and place. Highlights: Particular forms of masculinity continue to marginalise and erase emotion within the extractive sector. Hegemonic masculinities also shape how 'social impacts' are determined and mitigated within the extractive sector. When emotion is dismissed, the emotive and affective consequences of resource extraction are also devalued.